การศึกษาการพัฒนาพยาบาลวิชาชีพเข้าสู่ตำแหน่งหัวหน้าหอผู้ป่วย โรงพยาบาลศูนย์ - ไชยฤกษ์ ปราณีต; ประจุศิลป กัญญดา (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2015)
การวิจัยเชิงพรรณนาครั้งนี้ มีวัตถุประสงค์เพื่อ 1) ศึกษาการได้รับการพัฒนาเข้าสู่ตำแหน่ง ตามการรับรู้ของหัวหน้าหอผู้ป่วย โรงพยาบาลศูนย์ 2) ศึกษาการได้รับการพัฒนาเข้าสู่ตำแหน่ง ตามการรับรู้ของหัวหน้าหอผู้ป่วยโรงพยาบาลศูนย์ จำแนกตามอายุ ระดับการศึกษา ประสบการณ์ในการปฏิบัติการพยาบาล ประสบการณ์เป็นหัวหน้าหอผู้ป่วย และ 3) ศึกษาความคิดเห็นเกี่ยวกับความต้องการการได้รับการพัฒนาเข้าสู่ตำ แหน่งหัวหน้าหอผู้ป่วย โรงพยาบาลศูนย์ กลุ่มตัวอย่าง คือ หัวหน้าหอผู้ป่วย โรงพยาบาลศูนย์ จำนวน 264 คน ได้จากการสุ่มตัวอย่างแบบหลายขั้นตอน เครื่องมือที่ใช้ในการวิจัย คือ แบบสอบถามการได้รับการพัฒนาเข้าสู่ตำแหน่งตามการรับรู้ของหัวหน้าหอผู้ป่วย โรงพยาบาลศูนย์ ผ่านการตรวจสอบความตรงเชิงเนื้อหาจากผู้ทรงคุณวุฒิ จำนวน 5 คน ได้ค่าความตรงเชิงเนื้อหา เท่ากับ .88 และทดสอบความเที่ยงโดยหาค่าสัมประสิทธิ์แอลฟาครอนบาค ได้ค่าความเที่ยง .96 สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และไคสแควร์ ผลการวิจัยสรุปได้ว่า 1) การได้รับการพัฒนาเข้าสู่ตำแหน่ง ตามการรับรู้ของหัวหน้าหอผู้ป่วย โรงพยาบาลศูนย์อยู่ในระดับมาก ( = 3.54, S.D. = .81) 2) การได้รับการพัฒนาเข้าสู่ตำแหน่ง ตามการรับรู้ของหัวหน้าหอผู้ป่วย ตามผลดังนี้ 1) หัวหน้าหอผู้ป่วย อายุ 31-40 ปี และ 41-50 ปี อยู่ในระดับมาก ( = 3.67, S.D. = .44 และ = 3.62, S.D. = .61 ตามลำดับ) ส่วนอายุ 51-60 ปี อยู่ในระดับปานกลาง ( = 3.49, S.D. = .61) 2) หัวหน้าหอผู้ป่วยที่มีระดับการศึกษาปริญญาโท และปริญญาตรี อยู่ในระดับมาก( = 3.57, S.D. = .67 และ = 3.53, S.D. = .57 ตามลำดับ) 3) หัวหน้าหอผู้ป่วยที่มีประสบการณ์ในการปฏิบัติการพยาบาล มากกว่า 20 ปี, 11-20 ปี และ 1-10 ปี อยู่ในระดับมาก ( = 3.60, S.D. = .52, = 3.51, S.D. = .65 และ = 3.51, S.D. = .71 ตามลำดับ) 4) หัวหน้าหอผู้ป่วยที่มีประสบการณ์เป็นหัวหน้าหอผู้ป่วย 1-10 ปี และ 11-20 ปี อยู่ในระดับมาก ( = 3.58, S.D. = .55 และ = 3.51, S.D. = .66 ตามลำดับ) ส่วนผู้ที่มีประสบการณ์มากกว่า 20 ปี อยู่ในระดับปานกลาง ( = 3.36, S.D. = .83) และ 3) ความคิดเห็นเกี่ยวกับความต้องการการได้รับการพัฒนาเข้าสู่ตำแหน่งหัวหน้าหอผู้ป่วย ประกอบด้วย 3 ด้าน คือ 1) ด้านการพัฒนาความเป็นผู้นำ 2) ด้านการบริหารองค์กรพยาบาล และ 3) ด้านการพัฒนาคุณภาพการบริการพยาบาล A Study of the Development of Professional Nurses into Head Nurses Position, Regional Hospital. Abstract The purposes of this descriptive research were: 1) to explore the perceived the development of professional nurses into head nurse position, regional hospital, 2) to explore perceived the development of professional nurses into head nurse position, regional hospital, by age, educational level, experience in nursing, and experience as head nurse, and 3) to explore opinion on needs development of professional nurses into head nurse position, regional hospital. The population consisted of 264 head nurses. Research instruments was the development of professional nurses into head nurse position questionnaire which was tested for content validity and Cronbach’s alpha coefficients was .96. The data were analyzed using percentage, mean, standard deviation, Chi-square test and content analysis. The findings were summarized as follow: 1) The perceived the development of professional nurses into head nurse position, regional hospital was at the high levels ( = 3.54, S.D. = .81). 2) The perceived the development of professional nurses into head nurse position, regional hospital, the study findings indicated that: 1) For age groups, the 31-40 years old, and 41-50 years old perceived the development of professional nurses into head nurse position were at the high levels ( = 3.67, S.D. = .44 and = 3.62, S.D. = .61), and 51-60 years old perceived the development of professional nurses into head nurse position was at the moderate levels ( = 3.49, S.D. = .61). 2) For educational level, both master degree and bachelor degree perceived the development of professional nurses into head nurse position were at the high levels ( = 3.57, S.D. = .67 and = 3.53, S.D. = .57). 3) For experience in nursing, more than 20 years, 11-20 years and 1-10 years perceived the development of professional nurses into head nurse position were at the high levels ( = 3.60, S.D. = .52, = 3.51, S.D. = .65 and = 3.51, S.D. = .71). 4) For experience as head nurse, 1-10 years and 11-20 years were at the high levels ( = 3.58, S.D. = .55 และ = 3.51, S.D. = .66), and more than 20 years perceived the development of professional nurses into head nurse position was at the moderate levels ( = 3.36, S.D. = .83). And 3) The opinion on needs the development of professional nurses into head nurse position were developing leadership, nursing organizational administration, and improving the quality of nursing services.